Sleep Cycles and Health: Role of Sleep Stages, Circadian Rhythms, and Lifestyle Factors on Optimizing Physical Performance and Mental Well-Being – a literature review - Rutkowska, Marta; Bieńko, Mateusz; Król, Tomasz; Toborek, Michalina; Marchaj, Magdalena; Korta, Karolina; Putra, Anna; Niedziela, Natalia; Margas, Mikołaj; Bednarz, Karolina (Quality in Sport, 2024)
Introduction: Sleep is a crucial physiological process impacting cognitive function, emotional resilience, and physical health. It is fundamental to overall well-being and understanding its nuances is imperative for unraveling the secrets of restorative sleep. Purpose: This review explores sleep cycles, synthesizing research on physiology, variability, and Non-Rapid Eye Movement (NREM) / Rapid Eye Movement (REM) dynamics to understand optimal rest. It assesses how disruptions, from lifestyle or sleep disorders, affect overall health. State of Knowledge: Sleep behaviors vary among individuals, influenced by factors like age, environment, health and lifestyle. Aging leads to changes in sleep patterns, impacting sleep quality. Sleep disorders, such as epilepsy and apnea, significantly alter sleep architecture, illustrating the close link between health and sleep. Lifestyle factors, including diet, physical activity and drug use, affect sleep quality, emphasizing the need for promoting healthy habits. Conclusion : The comprehensive exploration of sleep architecture, individual variability in sleep patterns, circadian rhythms, age-related changes, impact of drugs and sleep disorders, sleep hygiene, and associations with mental health underscores the intricate relationship between sleep and overall well-being. Sleep disorders pose an increased risk for mental health disorders, such as anxiety, stress, depression and ADHD. Conversely, mental health issues can significantly affect sleep quality and patterns. Developing strategies to promote healthy sleep hygiene and lifestyle habits is crucial in improving sleep quality, ultimately contributing to enhanced mental health, physical performance and well-being.